2005
DOI: 10.1002/app.21486
|View full text |Cite
|
Sign up to set email alerts
|

Study of the electrical properties of flame retardant poly(vinylchloride) using positron annihilation lifetime spectroscopy

Abstract: ABSTRACT:Since the large fire at the Brown Ferry cable plant which occurred at noon on March 22, 1975 in Alabama, attention has been given to the use of flame retardant cable in buildings to meet fire safety requirements. Flame retardants are used in wire and cable applications to prevent the conversion of an electric spark into fire and subsequently to prevent the spread of fire throughout a structure along the wiring. There are many substances used as flame retardants in wires and cables. In Egypt, Multi-Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…The influence of the plasticization process on free volume in PVC using PAL measurement was investigated by Borek and Osoba. 16 The electrical properties of flame retardant PVC were studied by Mostafa et al 17 In our previous work, the correlation between the dielectric data and the positron annihilation data was established 18 on PVC doped with different concentrations of Al 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the plasticization process on free volume in PVC using PAL measurement was investigated by Borek and Osoba. 16 The electrical properties of flame retardant PVC were studied by Mostafa et al 17 In our previous work, the correlation between the dielectric data and the positron annihilation data was established 18 on PVC doped with different concentrations of Al 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The slight increase of elongation at break in CB-FRPVC and FRPVC-reactor samples may be due to the presence of Ca as filler, which gives a smooth surface and delays the brightness character for the two samples. 19 From the above results, it is concluded that the exposure to a total dose of 80 KGy confers satisfactorily mechanical parameters to PVC samples. Nevertheless, after gamma irradiation at 80 Kg, PVC samples lost the mechanical strength.…”
Section: Mechanical Properties Resultsmentioning
confidence: 88%
“…The acid must be stabilized or bound in the cable system to prevent corrosion of the conductor and to prevent further degradation of the polymer. It is well known that PVC material free from Pb degrades at 160 C. Addition of Pb stabilizer shifts degradation temperature up to 210 C. 19 Calcium in the form of calcium carbonate (CaCO 3 ) is added to PVC as filler, which gives a smooth surface and cost reduction. However, because of its spherical partial geometry, it does not significantly reinforce the compound and because of its high alkalinity, it can interfere with halogenated flame retardants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Positron annihilation lifetime spectroscopy (PALS), a non-destructive technique, measures the time interval between the arrival of a positron into a medium and its annihilation. The positron is a nuclear probe to investigate free volume in polymers [6][7][8][9][10][11][12]. As Mostafa et al noted, "When a positron is injected into polymers, it interacts with molecules by an inelastic collision process leading to their ionization and excitation" [9].…”
Section: Original Papersmentioning
confidence: 99%